Building on 'Red Dirt' Perspectives: What Counts as Important for Remote Education?. Issue 2 (3rd November 2015) - Guenther, John; Disbray, Samantha; Osborne, Sam
Abstract : The Remote Education Systems (RES) project within the Cooperative Research Centre for Remote Economic Participation (CRC-REP) has, over the last four years, gathered and analysed qualitative data directly from over 230 remote education stakeholders and from more than 700 others through surveys. The research was designed to answer four questions: (1) What is education for in remote Aboriginal and Torres Strait Islander communities?; (2) What defines 'successful' educational outcomes from the remote Aboriginal and Torres Strait Islander standpoint?; (3) How does teaching need to change in order to achieve 'success' as defined by the Aboriginal and Torres Strait Islander standpoint?; and (4) What would an effective education system in remote Australia look like? Based on this data, the paper reveals how perceptions differ for Aboriginal and Torres Strait Islander people from remote communities compared with people who come from elsewhere. The analysis points to the need for some alternative indicators of 'success' to match the aspirations of local people living in remote communities. It also points to the need for school and system responses that resonate with community expectations of education, and to develop narratives of aspiration and success alongside community views.